A4.3 Effects of anti-TNF therapy on markers of bone homeostasis in rheumatoid arthritis and ankylosing spondylitis. (13th February 2015) - Á, Horváth; Pusztai, A; Gulyás, K; Váncsa, A; Végh, E; Bodnár, N; Csomor, P; Pethő, Z; Juhász, B; Szentpétery, Á; Szamosi, S; Bhattoa, H; et al.
Abstract : Background and objectives: Uncoupling of bone resorption and formation has been associated with rheumatoid arthritis (RA) and ankylosing spondylitis (AS). Generalised bone loss and erosions are characteristic for RA, while in AS, bone formation overrides resorption. The RANKL/OPG and the Wnt/DKK-1/sclerostin systems have been implicated in disturben bone homeostasis in arthritides. Anti-TNF biologics may beneficially influence erosions and bone loss in RA, however, they have little effect on bone formation in AS. In the present study, we assessed the effects of 1-year anti-TNF treatment on various bone biomarkers. Patients and methods: Altogether 43 arthritis patients including 30 RA patients treated with either etanercept (ETN) or certolizumab pegol (CZP) and 13 AS patients treated with ETN were included in a 12-month follow-up study. Disease activity (DAS28 or BASDAI), CRP, IgM rheumatoid factor, anti-CCP, calcium (Ca), phosphate (P), osteocalcin (OC), P1NP, CTX, BNP, sclerostin (SOST), DKK-1, soluble RANKL (sRANKL), cathepsin K (cathK) and vitamin D3 (vitD) levels were assessed at baseline, as well as 6 and 12 months after treatment initiation. Results: Anti-TNF treatment was highly effective in both diseases, as the mean DAS28 decreased from 6.32 to 3.16 (p = 0.02) in RA, mean BASDAI decreased from 5.87 to 1.84 (p < 0.001) in AS. In RA, anti-TNF treatment significantly decreased DKK-1 (60.5 ± 28.9 pM and 54.7 ± 20.8 pM, p = 0.036) and CathK (28.7 ± 6.2 pm and 26.8 ± 4.0 pm, p = 0.014) but increased SOST (107.0 ± 47.5 pM and 131.2 ± 85.2 pM, p = 0.04) levels from baseline to 12 months, respectively. In RA, ETN and CZP treatment also increased OPG/sRANKL ratio after 6 months (51.9) vs. baseline (43.9) (p = 0.01). In AS, ETN therapy significantly increased the bone formation marker P1NP (49.4 ± 19.0 pM and 56.9 ± 28.7 pM, p = 0.03) and SOST (70.6 ± 29.0 pM and 82.4 ± 48.3 pM, p = 0.022) levels from baseline to 12 months, respectively. ETN therapy also increased OPG/sRANKL ratio after 6 months (44.5) and 12 months (46.9) compared to baseline (34.5) in AS (p < 0.01). Both baseline and 12-month SOST levels were significantly lower in AS compared to RA (p < 0.001). When RA and AS data were pooled, TNF inhibition resulted in significantly decreased DKK-1 (p = 0.035) and cathK (p = 0.008) but increased P1NP (p = 0.04) and SOST (p = 0.04) after 12 months. In this study, biologics did not affect Ca, P, OC, CTX, BNP, vitD levels. Conclusions: In a mixed cohort of RA and AS patients, anti-TNF therapy resulted in a restoration of bone homeostasis by decreasing DKK-1 and CathK, increasing P1NP, SOST and OPG/sRANKL ratio. Lower SOST levels in AS compared to RA, as well as the induction of bone formation over resorption may account for the inefficacy of TNF inhibitors on syndesmophyte formation in AS.